Fluidoterapia endovenosa no adulto em choque circulatório: elaboração de protocolo assistencial de enfermagem fundamentado na taxonomia NANDA-NOC-NIC - Jaffar, Marcus Vinicius Ferreira (2023)
Intravenous fluid therapy is considered a treatment of choice for circulatory shock whose objective is to increase preload and stroke volume, consequently generating an improvement in tissue perfusion. However, it is not necessarily beneficial considering that only half of patients respond adequately to this treatment, and its success depends on myocardial contractile function. In this context, the monitoring of the effects of fluid therapy, desired or not, can benefit from systematized and organized actions by nursing professionals because they are primarily responsible for identifying the hemodynamic repercussions associated with the administration of intravenous fluids. To this end, the use of nursing diagnoses, outcomes, activities and interventions guide the professional activity of nurses through standardized language. Objectives: To develop a nursing care protocol for intravenous fluid therapy in adult patients in circulatory shock based on the NANDA International (NANDA-I) nursing diagnoses, Nursing Interventions Classification (NIC), and Nursing Outcomes Classification (NOC) taxonomies. Methodology: This is a study for the elaboration and evaluation of a nursing protocol for intravenous fluid therapy in the adult patient in circulatory shock guided by four methodological steps: 1) Integrative literature review to identify clinical indicators related to intravenous fluid therapy of the patient in shock; 2) Cross-mapping of clinical indicators with nursing diagnoses available in the NANDA-International taxonomy and NIC interventions/activities and their links with NOC nursing outcomes; 3) elaboration of the care protocol based on the COREN/SP Guide for the Construction of Nursing Care Protocols and on the recommendations of the clinical guidelines evaluation tool, Appraisal of Guidelines for Research & Evaluation (AGREE II); 4) evaluation of the nursing care protocol for intravenous fluid therapy in patients in circulatory shock by judges. Results/Products: Construction of the Nursing Care Protocol for Endovenous Fluid Therapy in Patients in Circulatory Shock and its flowchart of use, in addition to two academic articles produced through the methodological steps of this study. Conclusion: It is expected that this product will be implemented in hospital institutions, contributing to nursing clinical practice through systematic clinical reasoning necessary for assistance as well as in the standardization of nursing activities through the application of the scientific method. This protocol, based on the diagnoses, results and nursing interventions, aims to improve the nurse's work methodology, and consequently the nursing team, enabling the reduction in the identification time of the main signs, symptoms and complications related to fluid therapy, promoting the improvement of the care provided and improving the outcomes of patients submitted to this therapy. The products of this research will be registered in the National Library and will be available for consultation on the website of the Graduate Program of the Professional Master's Degree in Nursing of the Federal University of Espírito Santo.